Numerical Investigation on Aerodynamic Drag and Noise of Pantographs with Modified Structures - Yao, Y.; Sun, Z.; Li, G.; Prapamonthon, P.; Cheng, G.; Yang, G. (My University, 2022)
It is well known that the pantograph, which works as a complex component of high-speed trains, is an important source of aerodynamic drag and aerodynamic noise of a high-speed train (HST) that can affect HST performance, comfort for passengers, and quietness of nearby communities. Thus, comprehensive studies on aerodynamic characteristics including aerodynamic drag and aerodynamic noise obtained by the pantograph need to be conducted. This work presents the aerodynamic characteristics including aerodynamic resistance and aerodynamic noise generated by the prototype pantograph of a high-speed train running at a speed of 300 km/h using numerical techniques of improved delayed detached-eddy simulation (IDDES) and acoustic finite element method (FEM). Then, the structure of the original pantograph is modified by wrapping the insulators, and the base frame, so that aerodynamic resistance and aerodynamic noise may be reduced as expected. Numerical results obtained from the pantograph without modification, with two modifications to the original design i.e. the base frame, and the insulators, are discussed. Compared to the original pantograph, the two modifications of the pantograph at the base frame and the support insulators are conducive to reducing the aerodynamic drag of the pantograph. However, the results also show that the modified insulator may not achieve considerable success in noise reduction. Only the modified base frame shows that noise is reduced significantly. Therefore, this suggests that the pantograph with base frame modification is a better choice for resistance and noise reduction.
Keywords: Acoustic finite element method; Aerodynamic noise; High speed train; Pantograph; Resistance